The Intention to Use E-Money using Theory of Planned Behavior and Locus of Control - Alfalia Citra Ayudya; Amin Wibowo (Jurnal Keuangan dan Perbankan, 2018)
Along with technological developments in the payment system, the role of cash as a means of payment began to be replaced by a more efficient and economical form of non-cash payment such as electronic money. However, the use of electronic money in Indonesia has not increased and the percentage of users of it is far behind compared with other countries. This study aims to apply the Theory of Planned Behavior (TPB) with Locus of Control (LOC) as a moderating variable in the context of the use of electronic money. The community of DIY consisted of 1 municipality and 4 districts were selected as the sample of this study. The results of this study indicate in general that the variable attitude to behavior as well as control of perceptive behavior have a positive effect on the intention of using electronic money while subjective norms are not proven to significantly affect the intention. However, especially for the respondents who live in the village, the subjective norm variable actually affects the intention of using the electronic money, while the variable control of perceptive behavior has no effect on the intention. Locus of Control (LOC) is not proven to moderate the existing variables in the Theory of Planned Behavior with the intention of using electronic money.JEL Classification: D91; O33; P25DOI: https://doi.org/10.26905/jkdp.v22i2.1691